Effect of Copper on the Grain Size and Tensile Strength of Ultra-low Carbon Steel - Bui, Anh-Hoa; Nguyen, Cao-Son (JST: Engineering And Technology For Sustainable Development, 2023)
This paper presents a study on the grain size and tensile strength of annealed ultra-low carbon (ULC) steel containing 0.008 wt.% carbon (C) and various contents of copper (Cu). The annealing temperature was predetermined at 700, 800, and 900 C with the same holding time of 15 minutes and a slow cooling rate. The microstructural result showed that the ferritic grain size of the steel increased with the annealing temperature, e.g. increased to 60 and 65 µm when the temperature raised to 900 C for the 0.112 and 0.285 wt.% Cu steel, respectively. This phenomenon was attributed to the recrystallization of the steel during the annealing process. The coarser grains resulted in a decrease in the tensile strength of the steel despite that the tensile strength of the steel was found to improve with the increased Cu content. The low tensile strengths and good elongation remained in the ULC steel, for instance, the ultimate tensile strength stayed in the range of 234-350 MPa and the elongation remained in the range of 22-35 % dependent on the annealed temperature, and the Cu content. The results show that the content of Cu less than 0.3 wt.% did not have a negative effect on the tensile strength of the studied steel, but caused a deteriorated elongation of the steels annealed at 900 C.